Vadba borilnih veščin za otroke in mladostnike - Besal, Sara (Šport (Ljubljana), 2024)
Martial arts can be used as a tool for development of strength, coordination, cardiovascular endurance, and agility in children and adolescents. For kids and adolescents are appropriate especially martial arts which do not involve striking and kicking, but rather focus on grappling, balance-breaking, throws, and controlling the opponent on the ground. Young people can engage in martial arts training at local clubs and martial arts schools, or they can learn the basics as part of physical education classes in elementary and secondary schools. The latter depends mainly on the experience or knowledge of the physical education teacher. Through such activities, children and adolescents learn the falling techniques and the basics of self-defence techniques, or they develop some components of physical fitness through various combat games. Soft martial arts have a traditional background, so in addition to knowing technical elements and improving certain motor skills, they promote social, emotional, mental development, as well as ethical and moral behaviour.
Keywords: adolescents; borilne veščine; children; martial atrs; mladostniki; otroci; physical fitness; social developmnet; socialni razvoj; sport; šport; telesna zmogljivost